The effect of realia on 9th students vocabulary learning at a public high school (2019)
This research is intended to use Realia as a possible strategy to improve the 9th- grade students’ vocabulary learning in a public high school in Sincelejo. The objective of this project is to describe the effect of Realia on the vocabulary learning process. To meet the general objective, researchers will identify the advantages and disadvantages of this strategy, analyze the changes in vocabulary learning and determine the effectiveness of Realia. For the development of this study, it will be implemented a descriptive qualitative approach implementing the characteristics of action research. A general population is a group of 9th-grade students who range in age from 13 and 16 years old. They consist of 34 students, but it was only taken a sample of 20 people. The research will be applied in 2 cycles which consist of 5 lesson plans each one. To accomplish the objectives, researchers will apply a students’ survey, level tests at the beginning of each process, some lessons using pictures and translation, other ones using Realia. Later, it will be applied some recall tests after each lesson.